Tourism Marketing Strategy In Ambon City - Albertus Lalaun; Victor Cornelis; Theofilus J.F.K. Matrutty (Brilliant International Journal Of Management And Tourism, 2023)
The increasing number of tourist destinations and investment makes the tourism sector a key factor in increasing foreign exchange, job creation, business development, and infrastructure. Indonesia, known as a country with a wide range of potential, is able to attract many people to come and explore its uniqueness. Not surprisingly, tourism has been made a priority development program that has always been targeted at achievement by the government. In the last five years, the number of tourist visits to Indonesia has continued to increase. This number of visits has definitely influenced the growth of foreign exchange in Indonesia. In 2021, Indonesian tourism will rank second as the country's foreign exchange contributor after the palm coconut sector, with a value of $20.9 billion. However, even though currency and tourist visits have increased, it turns out that not all Indonesians enjoy the "sweet cake" or the economic impact of tourism. The development of tourism has concentrated on priority tourist destinations. From the above phenomenon, it can be concluded that the most profitable tourism product for the tourism sector producer in Ambon City is to get the maximum benefit of the effort made to raise prices gradually by paying attention to other competitors in order to keep getting the fixed tourists. The combination of the production factors that must be chosen by the producer to get maximum profit, profit per unit of production can be maximum, but must prioritize the quality of production and the price to compete with other products.